Travails of Protest And Resistance: Mahasweta Devi‟s Breast Stories (International Journal of Psychosocial Rehabilitation, 2020)
Mahasweta Devi is a renowned woman writer, media person (journalist), and social campaigner who was born in 1926 in Bangladesh. She had a special place in her heart for the tribal people and spent her whole life working towards their social well-being. She was called ‘The Mother of the Sabars’ as she had worked very hard to make the lives of the people of the Sabar tribe better.